Chemical Vapor Deposition for Nanotechnology - Mandracci, Pietro (IntechOpen, 2019)
Chemical vapor deposition (CVD) techniques have played a major role in the development of modern technology, and the rise of nanotechnology has further increased their importance, thanks to techniques such as atomic layer deposition (ALD) and vapor liquid solid growth, which are able to control the growth process at the nanoscale. This book aims to contribute to the knowledge of recent developments in CVD technology and its applications. To this aim, important process innovations, such as spatial ALD, direct liquid injection CVD, and electron cyclotron resonance CVD, are presented. Moreover, some of the most recent applications of CVD techniques for the growth of nanomaterials, including graphene, nanofibers, and diamond-like carbon, are described in the book.